2018
DOI: 10.1021/acs.jpcc.7b12035
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition Synthesis of MoS2 Layers from the Direct Sulfidation of MoO3 Surfaces Using Reactive Molecular Dynamics Simulations

Abstract: Atomically thin MoS2 layer, a promising transition metal dichalcogenide (TMDC) material, has great potential for application in next-generation electronic and optoelectronic devices. Chemical vapor deposition (CVD) is the most effective technique for the synthesis of high-quality MoS2 layers. During CVD synthesis, monolayered MoS2 is generally synthesized by sulfidation of MoO3. Although qualitative reaction mechanisms for the sulfidation of MoO3 have been investigated by previous studies, the detailed reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…• Computationally efficient, high-performance & high-fidelity models to inform real-time control of 2D material growth • Computationally-informed reactor designs optimized for uniform growth conditions over large areas • Growth chamber database to reduce 2D material production time rate coefficients. This information can be obtained from atomistic simulations 128 or experiments such as mass spectroscopy. 129,130 The surface reactions involved also include chemisorption of gas-phase species and their reactions, desorption, and growth of the 2D material (Figure 4a).…”
Section: Milestonesmentioning
confidence: 99%
“…• Computationally efficient, high-performance & high-fidelity models to inform real-time control of 2D material growth • Computationally-informed reactor designs optimized for uniform growth conditions over large areas • Growth chamber database to reduce 2D material production time rate coefficients. This information can be obtained from atomistic simulations 128 or experiments such as mass spectroscopy. 129,130 The surface reactions involved also include chemisorption of gas-phase species and their reactions, desorption, and growth of the 2D material (Figure 4a).…”
Section: Milestonesmentioning
confidence: 99%
“…The COMB3 potentials have been used to simulate the experimental CVD deposition and growth of graphene and metal on substrates 98 . The ReaxFF potentials have been used to explore the structures of several 2D materials under intercalation, study the defects and groups on the surfaces of MXene materials, simulate CVD growth of MoS 2 layers, and explore the synthesis of 2D polymeric materials in experiments 7,99 . In general, COMB3 and ReaxFF can further explore 2D materials, as their functional forms can describe heterogeneous systems.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…[10,214] Direct quantum molecular dynamics (MD) simulations of growth are currently feasible, but often for system sizes and time scales that could presently be too small to be considered relevant for experimental conditions. This is why, in the literature, theoretical or modeling investigations dealing with nucleation and growth mechanisms at finite temperatures are significantly fewer [53,[223][224][225] than those dealing with the structure and properties of TMDs at zero Kelvin. We note, however, that ab initio quantum MD (QMD) simulations may be used to seek insights into the initial stages (small simulation times) of one or few precursor molecules reacting with the substrate.…”
Section: Simulations Of Tmd Growthmentioning
confidence: 99%
“…[230] With particular focus on TMDs, there is recent work by the Hong et al on the mechanism of sulfurization of MoO 3 . [223,225] They investigate the reaction mechanisms that occur during the deposition of S 2 gas at the surface of MoO 3 : although it is expected that sulfurization will occur, the key reaction events during this process have been studied with numerous gas molecules, by following molecular trajectories over time-scales of the order of ns. [223] They showed that reaction mechanisms and growth kinetics during sulfurization of…”
Section: Simulations Of Tmd Growthmentioning
confidence: 99%